Implementasi Nilai-Nilai Islam Moderat Dalam Pembentukan Karakter Moderat Siswa - Fazlurrohmah, Sabilun Najah; Rofiq, Mohammad (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2025)
This article aims to describe and analyze the implementation of moderate Islamic values in the formation of moderate character of students at SMP Negeri 2 Gresik. This research is qualitative in nature with the type of case study research and uses the single case study method. Data analysis techniques are data reduction, data presentation, conclusion drawing. The implementation of moderate Islamic values in the formation of moderate character of students at SMP Negeri 2 Gresik are: 1) Moderate Islamic values are applied in various school activities, such as the habituation of praying before and after learning and the routine of Dzuhur prayer in congregation. In addition, the concept of religious moderation is also realized through the Religious Moderation School program, which includes commemoration of religious holidays, introduction to religious diversity, religious literacy, and anti-bullying campaigns. All of these activities aim to shape students' characters to have a tolerant attitude towards others and avoid all forms of discrimination. 2) SMP Negeri 2 Gresik prioritizes moderate Islamic values, especially Tasamuh (tolerance) and I'tidal (justice), which are reflected in the education process and school activities. These two values become the main principles in every school activity and learning process. The application of these values can be seen in the character of students who show tolerance, justice, balance, love for peace, responsibility, democracy, free speech, and uphold a sense of brotherhood.